Status of Serum Vitamin B12 in Type 2 Diabetes Mellitus Patients under Metformin Therapy - Sah, Sanjay Kumar; Gupta, Suprita; Jha, Amit Chandra; Marasini, Surendra; Yadav, Tapeshwar; Shrestha, Brijesh (Nepal Journal of Health Sciences, 2022)
Introduction: Type 2 diabetes mellitus, a prevalent global health problem, is a major cause of morbidity and mortality. Metformin, the most widely used hypoglycemic agent can lead to a deficiency of vitamin B12. Very less information is available regarding the relationship between metformin therapy and vitamin B12 deficiency in the Nepalese population. Objectives: The study aims to evaluate the level of vitamin B12 in cases of diabetes mellitus under metformin therapy and to access the relationship of serum vitamin B12 level with the duration of metformin therapy. Methods: A hospital-based cross-sectional study with 300 diagnosed diabetes mellitus cases under metformin therapy were enrolled in the study after the consent was taken. The prior ethical clearance was taken and the duration of the study was from December 2021 to June 2022. Results: The study showed 78% (n=234) of the total diabetic cases under metformin therapy had lower vitamin B12. In 50-60 years, age group, 91% of them were vitamin B12 deficient. Vitamin B12 deficient cases were more with the increase in duration and dose of metformin therapy. All the diabetics who were under medication for 16-20 years had lower vitamin levels. About 94% (n=200) of the diabetics taking more than 1000 mg/day were vitamin B12 deficient whereas only 39% (n=34) of diabetics taking less than 1000mg/day were found to be deficient. Conclusions: Vitamin B12 is deficient in diabetics under long-term and higher doses of metformin therapy. Diabetic patients who are undergoing metformin treatment should monitor their vitamin B12 status as they are more prone to vitamin B12 deficiency.